Development of Integrated Transport Infrastructure Based on Supply-Demand Adaptability Analysis - Qian Li; Chunfang Lu; Huapu Lu; Yongbo Zhang; Jiawei Gui (中国工程科学)
The comprehensive transport infrastructure is an important component of the comprehensive transport system and is vital for economic and social development. This study reviews the current situation and problems of comprehensive transport development in China, quantifies the supply-demand adaptability of railways, highways, water transport, and civil aviation by using the utilization index, and proposes the development direction, construction focus, and policy suggestions for the transport infrastructure. The research indicates that China's transport infrastructure can basically adapt to economic and social development, but still cannot "fully adapt to people's growing needs for a better life", a target proposed in the Planning Outline for a Comprehensive National Transport Network. Among the different modes of transport, civil aviation, intercity railways, and common national highways are the ones with insufficient adaptability. Combined with the adaptability analysis of the infrastructure, this study clarifies the ideas and focuses of transport infrastructure construction and proposes to optimize the demand assessment, project decision, and integrated planning and construction mechanisms of the comprehensive transport infrastructure.